Integrating thin client solution in human-computer interaction study - Ahlan, Abdul Rahman; Arshad, Yusri; Mahmud, Murni (World Scientific and Engineering Academy and Society, 2010)
Over the past decades the field of education has witnessed the introduction of Internet, a new and revolutionary technology that seems to radically alter the way humans teach and learn. Offering thin client solution for Orang Asli provides opportunities for the team to undertake human-computer interaction related studies.Thin client is an effective and efficient ways to provide at least computer computers and internet facilities and infrastructure for organizations or communities. Orang Asli community is continuously given attention by the government for their development so as not to widen digital gap with other advanced race in Malaysia. IT education and access to computers and Internets seem to be one of the noble viable options for the young generations to nurture the knowledge society values.This is due to many adverse reports related to Orang Asli attitudes and behaviours in the media as well as research publications. Thus, our IT social inclusion project is timely and hoped to contribute to their development for better lives. This paper describes the proposed thin client configuration for Orang Asli community in Gombak area. It begins with literature reviews on previous studies, concepts and products available and description of Orang Asli schoolchildren in the area as well as introduction to human-computer interaction and usability testing and evaluation. Based on risk management assessment, thin client system is chosen for the community and the proposed architecture configuration is described and illustrated. The HCI is described and proposed for future research.